Processos de inclusão em atividades de educaçao em ciências : percursos e percalços vivenciados no projeto Novos Talentos – UFMT/CAPES - Lemos, Cassia Erika (2016)
Assuring the equality of conditions to the learning process is the order of educational inclusion. There is a knowledge which says the inclusion needs to occur in different places from the propositions of the educational institutions, for example the universities. In this fact, the inclusion needs to occur in three dimensions of academic life: teaching, searching and extension. This presented project tables the inclusion in the academic extension area. The objective is to analyze the deaf students’ comprehension, participants of the Project New Talents, about the proposal of developed inclusion in the alluded project, giving an emphasis to the activities relating to the environmental science education. This project sets itself as a developed activity in the central campus of Federal University of Mato Grosso promoted by Capes. The theoretical bases come from formulations of Deaf Studies and from the Vygotyskiana’s sociointeractionist conceptions, besides Attico Chassot’s conceptions of education in science. The research of the qualitative type used, as means of data collection, half structured individual interviewing and participative observation. Ten participants were interviewed, in which nine were deaf students, and one deaf teacher, in the Attendance and Support to the Auditory Deficient Center (Centro de Atendimento e Apoio ao Deficiente Auditivo), Teacher Arlete Pereira, from Cuiabá. The data analyses show that the inclusion is understood as an integration – which has always been significant for deaf people, once they see it as learning opportunities, as well as they feel comfortable, setting up, thus, as participative people in the inclusion process. Potential and challenges of the inclusion were identified. The potentialities of the including proposal of the extension project in screen were related to: motivation to apply for college; interaction with other people, giving an opportunity to new experiences; and access to the scientific culture with consequential learning in different areas of knowledge. The challenges needed to be overcome for the educational inclusion of deaf people were associated with the difficulties in the Portuguese Language comprehension during the activities of the project; limited interactions between deaf and auditory, due to the non-use of Brazilian Sign Language (BSL) by the listeners, as well as dependence on BSL interpreters in the activities, which refers to the operational limitation. Therefore, the presence of interpreters were settled as a fundamental condition to facilitate the interrelationship between the deaf and the listeners. In essence, the analyses show that the university extension is a possibility of inclusive propositions of deaf students in the university culture, at the same time that the deaf culture is noticed and, rightly, incorporated by the listener participants.